2018
DOI: 10.1016/j.vaccine.2017.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Burden of medically attended influenza infection and cases averted by vaccination – United States, 2013/14 through 2015/16 influenza seasons

Abstract: Background In addition to preventing hospitalizations and deaths due to influenza, influenza vaccination programs can reduce the burden of outpatient visits for influenza. We estimated the incidence of medically-attended influenza at three geographically diverse sites in the United States, and the cases averted by vaccination, for the 2013/14 through 2015/16 influenza seasons. Methods We defined surveillance populations at three sites from the United States Influenza Vaccine Effectiveness Network. Among thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 21 publications
2
18
0
1
Order By: Relevance
“…In the U.S., the Advisory Committee on Immunization Practices (ACIP) recommends annual influenza vaccination for all persons aged 6 months and older and prioritizes those at higher risk for influenza complications [10]. High-risk groups include adults aged > 65 years [11,12], children aged < 5 years (particularly those aged < 2 years) [13,14], pregnant women (up to 2 weeks postpartum) [15][16][17][18], persons with certain chronic medical conditions, Native Americans/Alaska Natives, 1 and residents of nursing homes and other long-term care facilities ( Table 2). Studies have specifically highlighted that those with chronic pulmonary, cardiovascular, renal, hepatic, neurologic, hematologic or metabolic disorders, immunocompromised persons, children and adolescents receiving aspirin-or salicylate-containing medications and who might be at risk for experiencing Reye syndrome with influenza virus infection, and those who are extremely obese (BMI > 40) are at increased risk for influenza-related complications [10,[19][20][21][22][23].…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the U.S., the Advisory Committee on Immunization Practices (ACIP) recommends annual influenza vaccination for all persons aged 6 months and older and prioritizes those at higher risk for influenza complications [10]. High-risk groups include adults aged > 65 years [11,12], children aged < 5 years (particularly those aged < 2 years) [13,14], pregnant women (up to 2 weeks postpartum) [15][16][17][18], persons with certain chronic medical conditions, Native Americans/Alaska Natives, 1 and residents of nursing homes and other long-term care facilities ( Table 2). Studies have specifically highlighted that those with chronic pulmonary, cardiovascular, renal, hepatic, neurologic, hematologic or metabolic disorders, immunocompromised persons, children and adolescents receiving aspirin-or salicylate-containing medications and who might be at risk for experiencing Reye syndrome with influenza virus infection, and those who are extremely obese (BMI > 40) are at increased risk for influenza-related complications [10,[19][20][21][22][23].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Annual seasonal influenza epidemics of variable severity result in significant morbidity and mortality in the United States (U.S.) and worldwide [1][2][3]. In temperate climate countries, including the U.S., influenza activity peaks during the winter months whereas in tropical regions influenza activity may be more variable [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccine effectiveness (VE) is influenced by viral subtype/lineage as well as the timing of vaccination (early or late epidemic in a season). VE of trivalent influenza vaccine (TIV) is assessed as from 20 to 50% in vaccine programs of several countries [6,7]. The population rate of people was over 80% in the Korean national immunization program but VE remains low in the elderly adults [8].…”
Section: Preventionmentioning
confidence: 99%
“…Prior research has shown AFV reduces the number of physician office visits,7 intensive care unit admissions,8 9 days spent in hospital8 9 and patient mortality 9. The CDC estimated influenza vaccinations prevented 84 700 hospitalisations and between 1588 and 4562 deaths during the 2016–2017 influenza season 10.…”
Section: Introductionmentioning
confidence: 99%
“…Given the benefits of AFV, vaccination rates in the USA have remained low. Between 2009 and 2017, less than 50% of US adults received an AFV 6 7 11–15. During the 2017–2018 influenza season, the coverage rate for adults ≥18 years was only 37.1% 16…”
Section: Introductionmentioning
confidence: 99%